Small-scale fishermen: Poverty as a challenge to achieve Sustainable Development Goals (SDGs) in Sunda Strait - Yonvitner Yonvitner; Hanif Wafi; Gatot Yulianto; Mennofatria Boer; Rahmat Kurnia (Faculty of Social and Political Science, Universitas Airlangga, 2021)
The poverty reduction indicator in SDGs also includes small-scale fisheries community groups. Small-scale fisheries’ poverty can be measured by income, expenditure, and income, converted to minimum living consumption and village welfare standards. These research aims to study of fisherman income, and welfare level as an indicator of poverty status. The research was conducted at the fisheries landing port in the Sunda Strait during 2019 to collect fisheries data covering production, operational cost, and household expenditure costs. The results showed that most ship crew fishers and ship captains (74%) were poor. Only 26% of the fishermen lived in no poverty status; however, all fishermen classified as high and medium welfare levels from the welfare indicator. Reducing poverty status (period 2020-2030) to be null (zero poverty) should be gradual with a yearly target. According to SDGs target, it needs comprehensive efforts to reduce poverty within ten years, with an average reduction of 7% per year until 2030. It means the government should implement the fishermen’s poverty reduction as part of the national development target.